The Role of Special Education Support Teachers in Enhancing Literacy Interest among Students with Special Needs in the School Environment - Siti Aminah Az Zahra; Arta Mulya Budi Harsono; Ahmad Suriansyah; Muhsinah Annisa; Latifa Putri Ridhaningtyas (Balai Publikasi Indonesia, 2025)
Education is the basic right of every child, including children with special needs, who have the right to receive a decent education in accordance with the 1945 Constitution. Along with the paradigm shift in basic education, the focus is now shifting towards inclusive learning that respects student diversity. The success of inclusive education really depends on the competence of teachers, especially Special Guidance Teachers (GPK), who play an important role in managing learning for students with special needs. By using a qualitative approach, this research was carried out at SD Negeri Melayu 11 with the aim of analyzing the effectiveness of the approach applied by ABK teachers in developing students' literacy skills, identifying supporting factors and obstacles in the literacy learning process, and providing strategic recommendations. to improve the quality of literacy teaching that is more focused and appropriate to the needs of students with special needs. The research results show that the use of learning methods that involve media has a significant influence on increasing literacy interest in children with special needs